Hypertension management in older adults [version 1; peer review: 5 approved] - Ozlem Bilen; Nanette K. Wenger (F1000Research, 2020)
Vascular aging leads to arterial hypertension, which is the leading cause of cardiovascular mortality and morbidity in older adults. Blood pressure reduction is effective in reducing the cardiovascular risk and is safe in ambulatory older adults. It is important to note that blood pressure control in this group of patients is challenging because of comorbidities, polypharmacy, and frailty. Choice of pharmacotherapy is not simple and should be individualized.